Communication strategies for moral rebels: How to talk about change in order to inspire self‐efficacy in others. (27th April 2022) - Brouwer, Claire; Bolderdijk, Jan‐Willem; Cornelissen, Gert; Kurz, Tim
Abstract: Current carbon‐intensive lifestyles are unsustainable and drastic social changes are required to combat climate change. To achieve such change, moral rebels (i.e., individuals who deviate from current behavioral norms based on ethical considerations) may be crucial catalyzers. However, the current literature holds that moral rebels may do more harm than good. By deviating from what most people do, based on a moral concern, moral rebels pose a threat to the moral self‐view of their observers who share but fail to uphold that concern. Those observers may realize that their behavior does not live up to their moral values, and feel morally inadequate as a result. Work on "do‐gooder derogation" demonstrates that rebel‐induced threat can elicit defensive reactance among observers, resulting in the rejection of moral rebels and their behavioral choices. Such findings suggest that advocates for social change should avoid triggering moral threat by, for example, presenting nonmoral justifications for their choices. We challenge this view by arguing that moral threat may be a necessary ingredient to achieve social change precisely because it triggers ethical dissonance. Thus, instead of avoiding moral justifications, it may be more effective to harness that threat. Ethical dissonance may offer the fuel needed for observers to engage in self‐improvement after being exposed to moral rebels, provided that observers feel capable of changing. Whether or not observers feel capable of changing, however, depends on how rebels communicate their moral choices to others—how they talk about change. This article is categorized under: Perceptions, Behaviour and Communication of Climate Change > Behaviour Change and Responses Abstract : How to talk about change: The importance of expressing moral motivations for change coupled with words of encouragement that others too can change.